ISU KEBEBASAN BERAGAMA DI INDONESIA DALAM KACAMATA FILSAFAT ZHUANGZI - Emanuel, Yohanes (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
The main focus of this paper is to examine the issue of religious freedom in Indonesia, which has recently shown a decline in tolerance between majority and minority religions. Religion essentially teaches faith and morality to its adherents, not a doctrine that creates hostility as is currently the case in Indonesia. The failure of the government and society to fight for religious freedom has resulted in disharmony in communal life, reflected in various incidents of discrimination, prohibitions on worship, and acts of intolerance that harm certain groups. This situation indicates a serious challenge in safeguarding human rights, particularly the right to embrace religion and practice worship according to one's beliefs. In response to this issue, the author seeks to examine three main questions: what is religious freedom? What is freedom according to Zhuangzi? And how is Zhuangzi's thinking on religious freedom implemented in Indonesia? Zhuangzi's thinking, which emphasizes inner freedom, acceptance of diversity, and rejection of coercion, serves as an important foundation for assessing the current situation of religious freedom in Indonesia. This research uses a literature study approach, utilizing sources in the form of relevant books, documents, and journals. It is hoped that this study can provide theoretical and practical contributions in building a peaceful, inclusive religious life, and upholding justice and freedom for every citizen.